2009
DOI: 10.2337/dc08-2305
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter 8 Antibodies Complement GAD and IA-2 Antibodies in the Identification and Characterization of Adult-Onset Autoimmune Diabetes

Abstract: OBJECTIVEZinc transporter 8 (ZnT8) is an islet β-cell secretory granule membrane protein recently identified as an autoantibody antigen in type 1 diabetes. The aim of this study was to determine the prevalence and role of antibodies to ZnT8 (ZnT8As) in adult-onset diabetes.RESEARCH DESIGN AND METHODSZnT8As were measured by a radioimmunoprecipitation assay using recombinant ZnT8 COOH-terminal or NH2-terminal proteins in 193 patients with adult-onset autoimmune diabetes having antibodies to either GAD (GADAs) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
96
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 14 publications
9
96
1
4
Order By: Relevance
“…Second, since GADA is not specific for autoimmune diabetes, a positive result could reflect an autoimmune tendency, independent of diabetes. Yet, in all the major studies of autoimmune diabetes, now amounting to many thousands of patients, those GADA-positive cases have a clinical phenotype different from that of the type 2 diabetic patients without GADA (15,22,24). Specifically, GADA-positive patients with adult-onset diabetes tend to have less metabolic syndrome and higher HbA 1c and are more likely to be on insulin therapy than GADA-negative patients with type 2 diabetesddifferences even apparent in patients with low-titer GADA.…”
Section: Resultsmentioning
confidence: 99%
“…Second, since GADA is not specific for autoimmune diabetes, a positive result could reflect an autoimmune tendency, independent of diabetes. Yet, in all the major studies of autoimmune diabetes, now amounting to many thousands of patients, those GADA-positive cases have a clinical phenotype different from that of the type 2 diabetic patients without GADA (15,22,24). Specifically, GADA-positive patients with adult-onset diabetes tend to have less metabolic syndrome and higher HbA 1c and are more likely to be on insulin therapy than GADA-negative patients with type 2 diabetesddifferences even apparent in patients with low-titer GADA.…”
Section: Resultsmentioning
confidence: 99%
“…Rapamycin was measured in whole blood using IMx sirolimus MEIA (Abbott Laboratories, Abbott Park, IL, USA). IA and GADA were determined by immunoprecipitation of recombinant antigens as previously described [20] and validated in the Diabetes Autoantibody Standardization Program (Laboratory 153) [21].…”
Section: Methodsmentioning
confidence: 99%
“…However, as many as 10% of new T1D patients may be negative for any of ICA, IAA, GADA or IA-2A. It has been suggested that the addition of ZnT8RA, ZnT8WA and ZnT8QA may improve the diagnostic sensitivity particularly in adults [20][21][22][23][24][25] The first aim of this study is to determine the diagnostic sensitivity of all three autoantibodies ZnT8RA, ZnT8WA and ZnT8QA and their relation to the other islet autoantibodies and HLA. Our second aim is to test if HLA DQ A1-B1 alleles, haplotypes or genotypes were associated with any of the ZnT8 autoantibodies.…”
Section: Introductionmentioning
confidence: 99%